The discursive construction of modern masculine identities in contemporary Malaysia - Nur Syuhada Mohd Radzi,; Bahiyah Dato’ Hj. Abdul Hamid,; Kesumawati Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In recent years, the emphasis on studies of western masculinities has caused studies on local masculinities not only to be ignored but marginalised. The underrepresentation of studies relating to Asian masculinity, particularly on Malaysian men, has caused a significant gap in theorizing about Asian men in general and Malaysian men in particular. With globalization and the shift in societal expectations of gender roles, men are urged to redefine and reconstruct their contemporary identities in their personal and professional lives. Despite the growing interest in masculine studies, research concerning men, especially in the social transformation of masculinity within the contemporary society is largely absent. This study examined the perceptions and experiences of Malaysian men in their negotiation of masculinity. Drawing from in depth semi structured interviews and content analysis of survey questions, the study explores the discursive construction of new masculinity among 28 Malaysian men aged between 25-35. Critical Discourse Analysis (CDA) was used for the analysis of interview transcripts. The study sought to investigate how new masculinity is constructed by analysing the interview discourse of the 28 respondents by paying close attention to the linguistic and lexical choices they used to describe masculine identities. This study examined whether the current notion of masculinity sustains or challenges the hegemonic concept. The findings of this study indicate that being seen as independent, competitive and a risk taker are among the important determinants of self-perceived masculinity. In some instances, traditional male identities which is linked with being dominant, muscular and being a provider are no longer considered as ultimate masculine identifications. The findings are of great importance to provide a refined and contextual understanding of how masculinity and complex male identities are constructed in contemporary society.